Diseño e Implementacion de un Modulo de Gestion de Energia para un Pico-Satelite Tipo Cubesat - Céspedes, Jorge Enrique Salamanca; Escobar, Roberto Ferro (KnE Engineering, 2018)
This article briefly describes the development of Power Module for Experimental picosatellite CubeSat UD Colombia 1 following CubeSat standard requirements. Whether the Power Module project consists of four stages of development: study, design, implementation and testing. In the study phase to review the theoretical framework and preliminary designs made in the Universidad Distrital and other CubeSat developed in the world, also investigates existing components and technologies in the market. The design phase involves analysis of the system and using a computer program designed to generate the necessary hardware. The implementation consists in making the printed circuit board and the component assembly. And electrical type tests to certify the proper operation of the module. The development of the power module of the CubeSat standard requirements and mission picosatellite, and depends on the state and information available from other modules picosatellite. The ultimate goal is to obtain a power module that is functional and working conditions of the space environment in which the picosatellite fulfill its focused on telemedicine, with a payload that would become the telecommunications system mission. Keywords: Power Module, CubeSat UD Colombia 1, Standard CubeSat, DC-DC converters, Solar Panels, Batteries, Power Management.